1960
DOI: 10.1080/00437956.1960.11659741
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Circle of New York

Abstract: During the academic year 1959-60 the monthly meetings of the Circle took place, as usual, between 2 and 4 p.m. on the second Saturday of each month from October through April in the auditorium of the French Consulate, 934 Fifth Avenue at 75th Street, New York City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Also, they [8] found that many 1+1dimensional integrable equations like KdV, Burgers, Sawada-Kotera, Harry-Dym hierarchies and Camassa-Holm equations arise from motions of plane curves in centro-affine, similarity, affine and fully affine geometries. The motion of curves on two-dimensional surfaces in E 3 1 was considered by Gürses [18]. Therefore, the motion of Lorentzian similar (null and nonnull) curves in Lorentzian-Minkowski similarity geometries will be investigated as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they [8] found that many 1+1dimensional integrable equations like KdV, Burgers, Sawada-Kotera, Harry-Dym hierarchies and Camassa-Holm equations arise from motions of plane curves in centro-affine, similarity, affine and fully affine geometries. The motion of curves on two-dimensional surfaces in E 3 1 was considered by Gürses [18]. Therefore, the motion of Lorentzian similar (null and nonnull) curves in Lorentzian-Minkowski similarity geometries will be investigated as well.…”
Section: Discussionmentioning
confidence: 99%
“…Berger [3] represented the broad content of similarity transformations of Euclidean space. Encheva and Georgiev [12,13] studied the differential geometric invariants of curves according to a similarity in the Euclidean n-space.…”
Section: H S ¸Ims ¸Ekmentioning
confidence: 99%
“…It can be separated to the four different cases as the following. We can take the initial conditions (17) in the example 8 for the all cases. Case 1: Let's take κγ 1 = 0 and τγ 1 = 0.…”
Section: Self-similar Null Cartan Curvesmentioning
confidence: 99%
“…Berger [17] represented the broad content of similarity transformations in the arbitrary dimensional Euclidean spaces. Encheva and Georgiev [21,22] studied the differential geometric invariants of curves according to a similarity in the finite dimensional Euclidean spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The broad content of similarity transformations were given by [5] in the Euclidean space. The differential geometric invariants of space curves according to the group of similarities were studied by [7] in the Euclidean 3-space.…”
Section: Introductionmentioning
confidence: 99%